DIGITAL LAW AND NORM-MAKING - Azizjon Khujanazarov (Modern American Journals, 2025)
This scientific article provides a detailed scientific analysis of the state of law in the era of modern trends and issues of digitalization. The article also provides a detailed scientific and legal analysis of the activities of rulemaking, which is one of the main areas of law enforcement, and the application of digital technologies in this area.
Keywords: Law, law, digitalization, trend, state, norm.